Sunday

April 20, 2014

April 20, 2014

Posted by **maura** on Thursday, September 20, 2012 at 6:49pm.

y = (Square root x)(x − 10)

- calculus -
**Reiny**, Thursday, September 20, 2012 at 7:23pmuse the product rule on

y = (x^(1/2))(x-10)

dy/dx = x^(1/2) (1) + (1/2)x^(-1/2) (x-10)

= (1/2) x^(-1/2) ( 2x + x-10)

= (3x-10)/(2√x)

- calculus -
**michelle**, Thursday, September 20, 2012 at 8:16pmThank you so much! I didn't think to use the product rule.

**Related Questions**

Trigonometry - Given the rectangular-form point (–1, 4), which of the following ...

Calculus - Find the point on the line 6x + y = 9 that is closest to the point (-...

calculus - how can I determine the domain of a function h(x): integrate from 0 ...

Algebra - Rationalize each expression by building perfect nth root factors for ...

Math simplifying mixed radicals - Please help me simplify these following mixed ...

calculus - Find the limit. lim h → 0 square root (49 + h) − 7 / h ...

Calculus - Find the derivative of f(x)=sqrt(9−sinx/1−cosx) Everthing...

math, calculus - find the derivative of the function y= integral from square ...

pre-calculus - Please diregard the other one the square root sign did not come ...

calculus - Determine an appropriate linear approximation of the function f(x)= ...